Internal and External Cooperation in Private Islamic Religious Colleges (STAI Pati’s Efforts Towards Competitive Advantage) - Ambarwati; Mu’arif, Samsul; Yulikah, Anik (Interdisciplinary Journal of Social Science and Education (IJSSE), 2024)
This research is motivated by the condition of Private Islamic Religious Colleges including Pati Islamic College which is relatively limited, where the development costs only come from student payments, so of course the situation is very different when compared to State Islamic Religious Colleges (PTKIN) when viewed from the side of facilities, infrastructure and other budgets. to support existence and competitive advantage, it is necessary to cooperate with other agencies. This study aims to determine the form of cooperation carried out by Pati Islamic College and its implementation both internally and externally. This is important to study, because Pati Islamic College is a private Islamic College which has several limitations compared to State Universities when facing various problems and challenges in improving quality towards competitive advantage. This research is a descriptive qualitative research with data sources obtained from interviews, observations and documentation. The results of this study indicate that efforts to increase competitive advantage are carried out by optimizing cooperation starting from the strengths and needs within the institution, good cooperation management based on mutually beneficial commitments and also to lead to institutions that are widely known to the public and have competitiveness. The form of cooperation is carried out in academic and non-academic fields, both internally and externally. Internal cooperation is carried out between study programs or between institutions that still exist within the Higher Education environment itself, while external cooperation is carried out between universities. All cooperation carried out refers to the Tri Dharma of Higher Education, namely, education and teaching, research and community service.